High treason [large type] - Mills, DiAnn (Mills, DiAnn. FBI Task Force, 2018)
"When Saudi Prince Omar bin Talal visits Houston seeking cancer treatment for his mother, an assassination attempt puts all agencies on high alert. FBI Special Agent Kord Davidson and CIA operative Monica Alden put aside interagency squabbles to find who is trying to stop the prince's plans to promote stronger ties with the US."--